Occupation-specific south-north migration - Nina Heuer (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2010)
This paper presents occupation-specific data on south-north migration around the year 2000 using employment data for developing sending and OECD receiving countries from ILO and OECD. These data reveal that the incidence of south-north migration was highest among professionals, one of the two occupational categories generally requiring tertiary education, and among clerks and legislators, senior officials and managers. At a more disaggregated level, I find that the probability that a professional in the OECD worked as a physical, mathematical and engineering science professional or as a life science and health professional was significantly larger for south-north migrants compared to OECD natives. It is exactly these occupational categories, characterized by internationally transferable skills, that exhibited significantly larger brain drain rates than teaching professionals, whose skills are rather country-specific. The employment shares of most types of professionals and technicians and associate professionals, as well as of clerks and corporate managers were significantly smaller in the migrant-sending countries compared to the receiving countries. The data further suggest a non-negligible brain waste due to imperfect transferability of skills acquired through formal education, since south-north migrants with a university degree more often worked in occupational categories requiring less than tertiary education compared to OECD natives.
urn:nbn:de:bsz:21-opus-47906
Keywords: F22; J24; O15; 330; international migration; brain drain; human capital; transferability of skills; occupational employment structure; Brain Drain; Auswanderung; Berufsstruktur; Entwicklungsländer; Einwanderung; Facharbeiter; Überqualifikation; Nord-Süd-Beziehungen; OECD-Staaten